O espaço público e sua relação com a segurança pública: um estudo de caso no bairro Jorge Teixeira, em Manaus/AM - Cavalcanti Junior, José Divanilson (2017)
The development of this study was based on the questions that arise after the frequent narratives of lynching episodes, many with fatal victims, and the lack of a culture of peace, socially balanced by order and security, that should be provided by the institutions formal or social production produced in the healthy social environment, propitiating the so-called informal control, emerged and fed within the community, mainly in the populous urban centers. A reflection on the collapse of security mechanisms, expressed in Foucault's thought, where we perceive that existing legal mechanisms are not sufficient to deal with problems arising from the multiplicity or plurality of criminality, nor can they recognize and validate the historical progress of recognition universal human rights. The fundamental right to security, which is constitutionally foreseen in our Constitution, is becoming a reality that is increasingly different from that of the 1988 legislator. Formal agencies (judiciary, prosecutor, police, etc.) are ineffective antidotes in producing the effect intended, unilaterally, to produce the desired result.